Metabolomics Reveals Effect of Zishen Jiangtang Pill, a Chinese Herbal Product on High-Fat Diet-Induced Type 2 Diabetes Mellitus in Mice - Chen, Jianping; Zheng, Lin; Hu, Zhaoliu; Wang, Fochang; Huang, Shiying; Li, Zhonggui; Zheng, Ping; Zhang, Shangbin; Yi, Tiegang; Li, Huilin (Frontiers in Pharmacology, 2019)
A Chinese herbal decoction, Zishen Jiangtang Pill (ZJP), has been clinically prescribed to diabetic patients to prevent excessive blood sugar levels for decades. However, the potential mechanisms of this action have not been well investigated. The purpose of this study was to explore the metabolic variations in response to ZJP treatment for an animal model of obese type 2 diabetes. An UHPLC-Orbitrap/MS-based metabolomics tool was conducted to reveal the potential mechanisms of ZJP on diabetic mice. The treatment with ZJP significantly restored the increased levels of insulin, glucose and total cholesterol in high-fat diet mice. A total of 26 potential biomarkers were found and identified in serum samples, amongst which 24 metabolites were robustly affected and driven back to the control-like levels after ZJP treatment. By analyzing the metabolic pathways, glutathione metabolism, steroid hormone biosynthesis and glycerophospholipid metabolism were suggested to be closely involved in diabetes disease. From the above outcomes, it can be concluded that ZJP exhibits a promising anti-diabetic activity, largely due to the regulation of phospholipid metabolism, including phosphatidylcholines, lysophosphatydylcholines, and phosphatidylinositol.